Cover Image. (12th April 2020) - Ferrada, Pablo; Rudolph, Dominik; Portillo, Carlos; Adrian, Adrian; Correa‐Puerta, Jonathan; Sierpe, Rodrigo; del Campo, Valeria; Flores, Marcos; Corrales, Tomas P.; Henríquez, Ricardo; Kogan, Marcelo J.; Lossen, Jan
Abstract : The cover image is based on the Research Article Interface analysis of Ag/n‐type Si contacts in n‐type PERT solar cells by Pablo Ferrada at al., https://doi.org/10.1002/pip.3242 .